"I don't get it", – the challenge of teaching reflective practice to health and care practitioners. Issue 2 (3rd March 2016) - Eaton, Colette
Abstract: Reflective practice is regarded as a fundamental learning tool that encourages the synthesis of theory and skills in healthcare and written reflective accounts feature heavily in the assessment of skills and development in practice. It is, however, a challenging method of teaching and learning for both students and educators and the reflective accounts produced are often superficial descriptions of events rather than evidence of 'reflection in action'. Revisiting writers such as Dewey, Rogers, and Schön, I present my own reflective account of teaching health-care students to develop reflective thinking and writing and finding ways of using mindfulness and sensory experience to bring reflection-in-action into the classroom. I conclude by suggesting that, as an educator, I have a responsibility to encourage and value subjective experience as evidence of learning.